Efficiency of Amino Acid Utilization in Nellore Cattle Grazing Low-Quality Forage Supplemented with Different Sources of Nitrogen - Dias, Ana Veronica Lino [UNESP]; Messana, Juliana Duarte [UNESP]; Granja-Salcedo, Yury Tatiana [UNESP]; Alfonso, Yeison Fabian Murilo [UNESP]; Silva, Lorrayny Galoro [UNESP]; Camargo, Karine Dalla Vecchia [UNESP]; Alves, Kênia Larissa Gomes Carvalho [UNESP]; Gonçalves, Paloma Helena [UNESP]; Reis, Ricardo Andrade [UNESP]; Berchielli, Telma Teresinha [UNESP] (MDPI, 2023)
This study aimed to evaluate the effects of supplementation with non-protein nitrogen (NPN) or ruminal undegradable protein (RUP) on intake, digestibility, and amino acid (AA) use efficiency of Nellore cattle grazing during the dry season. Eight Nellore steers (12 ± 2 months old) were used in quadruplicate Latin squares (2 × 2). The animals were placed on Urochloa brizantha cv. Xaraés under continuous grazing. The treatments included the following: (1) urea supplementation (NPN) and (2) supplementation of corn gluten meal 60 (CGM, RUP). Animals supplemented with CGM showed higher intakes of dry matter (DM) supplement, total AA, essential AA, and individual AA. The supplementation did not affect the total AA digestibility, total AA flux, and the AA fluxes of microbial origin and RUP from the diet (p > 0.05). The ruminal microorganism origin flux of total AA to the duodenum was 44.5% and 52.7% for animals supplemented with NPN and CGM, respectively. Animals supplemented with CGM showed an increase in blood concentrations of isoleucine (+19.09 μmol/L), cystine (+27.29 μmol/L), and albumin (+0.11 g/dL) (p < 0.05), but this increase was not accompanied by an improvement in N use efficiency of steers (p > 0.05). RUP supplementation via CGM can be an efficient nutritional strategy to enhance the intake and absorption of AA by Nellore cattle grazing low-quality forage during the dry season.
Keywords: corn gluten meal; digestibility; duodenal flow; Nellore; rumen undegradable protein; urea